1988
DOI: 10.1002/jnr.490190413
|View full text |Cite
|
Sign up to set email alerts
|

Taurine and nifedipine protect retinal rod outer segment structure altered by removal of divalent cations

Abstract: A protective effect of taurine on morphological alterations induced in isolated ROS by remotion of divalent cations is described. ROS damage is not observed when sodium or chloride is replaced by impermeant ions or in the presence of nifedipine (10 microM). An increased accumulation of 22Na but not of 36Cl occurs in retinas incubated in divalent cation free medium. Taurine (5-25 mM) provides a concentration-dependent protection to ROS structure. Taurine is also able to reduce the increased 22Na influx to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Retina is one of the sites that take up taurine with a high affinity (2)(3)(4). It has been reported that the release of taurine from a retinal preparation is induced by light stimulation (5), electrical stimulation to photoreceptor cells (6) or addition of K+ ions to the medium (7), and that taurine exhibits protective effects against the degeneration of photoreceptor cells caused by light stimulation (8), superoxide (9) or osmotic im balance (10). Therefore, taurine is thought to be re leased by certain light stimuli and to exhibit a protec tive role against photochemical damage of the photore ceptor membrane (11,12).…”
mentioning
confidence: 99%
“…Retina is one of the sites that take up taurine with a high affinity (2)(3)(4). It has been reported that the release of taurine from a retinal preparation is induced by light stimulation (5), electrical stimulation to photoreceptor cells (6) or addition of K+ ions to the medium (7), and that taurine exhibits protective effects against the degeneration of photoreceptor cells caused by light stimulation (8), superoxide (9) or osmotic im balance (10). Therefore, taurine is thought to be re leased by certain light stimuli and to exhibit a protec tive role against photochemical damage of the photore ceptor membrane (11,12).…”
mentioning
confidence: 99%